Effectiveness of Interactive E-Book Global Warming and Climate Change Integrated Socio Scientific Issues Peat Ecosystem - Maolina Asi; Amin Retnoningsih; Andin Irsadi (Postgraduate, University of Mataram, 2021)
Efforts to overcome global warming and climate change are integrated with science learning with the socio-scientific issues method. Materials on global warming and climate change are included in an interactive e-book that integrates the peat ecosystem's socio-scientific issues (SSI). This study aims to determine the effectiveness of the Integrated Interactive E-book SSI Ecosystem Peat on learning outcomes and students' environmental care attitudes. The research subjects were 30 grade VII students of SMPN 5 Palangkaraya, Central Kalimantan. The result is that SSI's integrated interactive e-book is effective in improving learning outcomes. The results of the SPSS test with a significance value of 0.05 showed a value of 0.008. There is a difference in the mean of the pretest and posttest results, with an N-gain value of 1.66 with low criteria. SSI's Integrated Interactive E-book is effective to improve students' environmental care attitude with an average score of 89.8% with the criteria of being very caring